Godfrey's narrative of the last Grinnell Arctic Exploring Expedition in search of Sir John Franklin, 1853-4-5 : with a biography of Dr. Elisha K. Kane, from the cradle to the grave - Godfrey, Wm. C. (William C.) (Philadelphia : J. T. Lloyd, 1857)
Mode of access: Internet.